Leukocyte telomere length and risk of coronary heart disease and stroke mortality: prospective evidence from a Russian cohort. Issue 1 (December 2018) - Stefler, Denes; Malyutina, Sofia; Maximov, Vladimir; Orlov, Pavel; Ivanoschuk, Dinara; Nikitin, Yury; Gafarov, Valery; Ryabikov, Andrey; Voevoda, Mikhail; Bobak, Martin; Holmes, Michael
Abstract Previous studies suggest that reduced leukocyte telomere length (LTL) is related to higher risk of mortality and several chronic conditions, including coronary heart disease (CHD) and stroke. However, the consistency of this association differs across populations. We investigated the relationship of LTL with CHD, stroke and all-cause mortality together with non-fatal CHD and stroke events in a Russian cohort with a mean age of 58 years at baseline. Data from 1, 144 individuals in the Russian subset of the Health Alcohol and Psychosocial Factors in Eastern Europe (HAPIEE) cohort study were used. The associations between LTL at baseline and fatal/non-fatal outcomes during 12 years of follow-up were assessed using multivariable Cox regression models, which yielded adjusted hazard ratios (HR). Compared to individuals in the shortest tertile, those in the longest tertile of LTL had a 42% lower risk of death from all-causes (HR 0.58; 95% CI: 0.39–0.88) and 58% lower risk of death from CHD (HR 0.42; 95%CI: 0.19–0.97). Similar patterns of association were identified for non-fatal and combined fatal/non-fatal CHD and stroke events but the associations were weaker. Consistent with results of previous studies in Western populations, this cohort of elderly Russian adults found an inverse association between LTL and CHD and all-cause mortality. These findings reinforce the hypothesis that LTL may play (or be a marker of) an aetiological role in human health across diverse populations.